Analisis Efektivitas Tugas Ramp Dispatcher dalam Mengupayakan On Time Performance (OTP) Oleh PT Gapura Angkasa - Sitio, Benediktus; Fatchul Hilal, Raden (Journal of Comprehensive Science, 2025)
This study discusses the problems tah hider the effectiveness of Ramp Dispatcher tasks, especially related to the failure to On Time Performance (OTP). The main problems identified are limited equipment and manpower. The purpose of this study is todetermine the effectiveness of the task, the obstacles faced, and the solutions implemented by Ramp Dispatcher officer of PT Gapura Angkasa in striving to achieve OTP. This study wa conducted at the PT Gapura Angkasa Operations Unit at Kualanamu Internasional Airport, Medan. The metod used in this study is data analysis with a qualitative descriptive approach, with primary data sources obtained through observation of the reasearch object and direct interviews with Ramp Dispatcher officers. Secondary data sources are obtained from documentation in the form of ramp activity checklists, Fueling orders, flight Schedules that include equipment and manpower readines checks, and related data before handling is carried out. The results of this study are regarding the Effectiveness of Ramp Dispatcher Tasks in striving for On Time Performance (OTP), namely by first conducting a Briefing On Spot (BOS) to ensure taht the entire team  is aware of the aircraft handling plan and supervising and coordinating all activites in the ram area, both those related to aircraft departures and arrivals. In the face of obstacles, Ramp Dispatcher coordinates with other teams regarding the use of equipment and availability of manpower, and prioritizes the use of aquipment and manpower on the aircraft that departed earlier. In addition, boarding management and the addition of human resources (HR) are carried out to provide encouragement to available officer.